2016
DOI: 10.18632/oncotarget.11601
|View full text |Cite
|
Sign up to set email alerts
|

SHP-2 phosphatase contributes to KRAS-driven intestinal oncogenesis but prevents colitis-associated cancer development

Abstract: A major risk factor of developing colorectal cancer (CRC) is the presence of chronic inflammation in the colon. In order to understand how inflammation contributes to CRC development, the present study focused on SHP-2, a tyrosine phosphatase encoded by PTPN11 gene in which polymorphisms have been shown to be markers of colitis susceptibility. Conversely, gain-of-function mutations in PTPN11 gene (E76 residue) have been found in certain sporadic CRC. Results shown herein demonstrate that SHP-2 expression was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…The complete mating information is available in supplementary material, Supplementary materials and methods. In brief, to express an active Shp‐2 protein in IEC, knock‐in Ptpn11 E76KNeo/+ mice were crossed with Villin‐Cre mice to generate double heterozygous experimental mice ( Shp‐2 IEC‐E76K ) and control littermates . The Shp‐2 deletion model was previously described ( Shp‐2 IEC‐KO ) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete mating information is available in supplementary material, Supplementary materials and methods. In brief, to express an active Shp‐2 protein in IEC, knock‐in Ptpn11 E76KNeo/+ mice were crossed with Villin‐Cre mice to generate double heterozygous experimental mice ( Shp‐2 IEC‐E76K ) and control littermates . The Shp‐2 deletion model was previously described ( Shp‐2 IEC‐KO ) .…”
Section: Methodsmentioning
confidence: 99%
“…Colons and ileums were fixed, sectioned and stained as described previously . Immunohistochemistry was performed using a DAKO EnVision+ System kit (Lexington, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…However, Kim et al suggested that SHP2 acts as a negative regulator of the JAK‐STAT signaling pathway, inhibiting inflammation in small glial cells. It has also been reported that IEC‐specific knockout of SHP2 (SHP2IEC‐KO) causes inflammation in mice and that this can result in spontaneous CRC after 15 months. However, in another in vitro experiments, the authors silenced SHP2 expression in IECs transfected with KRAS (IEC‐6/KRAIG) and in colon cancer cell lines and observed that this inhibited the malignant behavior of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…PTPN11 mutations have been extensively investigated in the past years. Germline mutations in PTPN11 cause Noonan syndrome (9)(10)(11) and its clinically related Leopard syndrome (12), whereas somatic mutations of PTPN11 contribute to leukemogenesis (13)(14)(15)(16)(17), as well as in the development of specific solid tumors, including neuroblastoma (18,19), metachondromatosis (20,21), brain tumors (22)(23)(24), neurofibromatosis (25), optic nerve pilomyxoid astrocytoma (26), breast carcinoma (27,28), colorectal cancer (29,30) and Ewing sarcoma (31). However, oncogenic mutations of PTPN11 are rare in the majority of solid tumors including GC (32,33).…”
Section: Introductionmentioning
confidence: 99%